2012
DOI: 10.1007/s11103-012-9898-x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiles and their control of male gametophyte development in rice

Abstract: Plant microRNAs (miRNAs) act as negative regulators of gene expression by slicing target transcripts or inhibiting translation. A number of miRNAs play important roles in development. In order to investigate the potential function of miRNAs during male gametogenesis in rice, we obtained both gene and small RNA expression profiles by combining microarray and high-throughput sequencing technologies. From the microarray datasets, 2,925 male gametophyte-specific genes were identified, including 107 transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 86 publications
3
22
0
Order By: Relevance
“…High levels of OsSUT5 transcripts were also detected in ovary and stigma during fertilization and embryogenesis (Figure 5A). Similar spatiotemporal expression patterns were observed in indica rice (Wang et al, 2010; Peng et al, 2012) (data not shown). The complementary expression patterns of clades P2 and P3 SUTs in reproductive tissues are consistent with subfunctionalization following their divergence from clade P1 by positive selection in monocots.…”
Section: Resultssupporting
confidence: 84%
“…High levels of OsSUT5 transcripts were also detected in ovary and stigma during fertilization and embryogenesis (Figure 5A). Similar spatiotemporal expression patterns were observed in indica rice (Wang et al, 2010; Peng et al, 2012) (data not shown). The complementary expression patterns of clades P2 and P3 SUTs in reproductive tissues are consistent with subfunctionalization following their divergence from clade P1 by positive selection in monocots.…”
Section: Resultssupporting
confidence: 84%
“…There was a major peak at 24 nt in the total small RNAs from our sRNA libraries (Fig. 2), consistent with previous results on rice (Peng et al 2012), soybean (Song et al 2011), cotton (Yin et al 2012), Medicago truncatula (Eyles et al 2013) and a recent research on tomato (Zuo et al 2012). One possible reason for the prevalence of 24 nt sRNA is that 24 nt sRNA is involved in heterochromatin modification, in particular for genomes with high repetitive sequence content (Schauer et al 2002;Jia et al 2009).…”
Section: Autoregulation Of Mirna Biogenesissupporting
confidence: 91%
“…For rice, 137 microarray samples from four data series (GEO accession numbers: GSE14304 [Fujita et al, 2010], GSE17002 [Russell et al, 2012], GSE27988 [Wei et al, 2010], GSE29212 [Peng et al, 2012]) were obtained and classified into 18 groups of tissues. For Arabidopsis, 244 microarray samples from seven data series (GEO accession numbers: GSE5630, GSE5631, GSE5632, GSE5633, GSE5634 [Schmid et al, 2005]; GSE6162 [Honys and Twell, 2004]; GSE17343 [Qin et al, 2009]; ArrayExpress accession: E-ATMX-35 [Borges et al, 2008]) were obtained and classified into 22 tissue groups.…”
Section: Microarray Data Set Preparation and Data Analysismentioning
confidence: 99%